Coverage of feminicides by the G1 portal in the state of Rio de Janeiro: Analysis based on a semiotics of violence in social representations (Research, Society and Development, 2025)
The objective of this work is to analyze the social representations of the crime of feminicide in the Brazilian press, based on the production of a specific wide-reaching media outlet throughout journalistic articles published throughout the year 2023 regarding cases that occurred in the state of Rio de Janeiro. We theorize the proposal based on semiotics and social representations with the aim of considering gender violence in journalistic perception. Methodologically, we apply content analysis by categorizing the reports in their victimological profile, in the context of the criminological design of the crime and in the journalistic delimitation of the content producer. As main results, we highlight that feminicide in the pages of newspapers presents critical discrepancies regarding its empirical statistical meaning and regarding the consolidated literature, while at the same time reinforcing it. On the other hand, the Brazilian press, while exposing the victim, displaces the aggressor and disfigures a crime by presenting a victim, an act committed and disappearing with the aggressor and his motivation.